The Effects of Climate Change on the Water Requirement of Potato Plants (Case Study: South of Kerman Province) - Fatemeh Bayatani; Keramat Nezhad Afzali (Sustainable Earth Trends)
Potato is considered a strategic product in providing food security in the future. Considering the phenomenon of global warming and affecting the production of agricultural products, it is necessary to evaluate its effects on potato production in the country. For this purpose, CanESM2 climate model data were used under RCP4.5, RCP2.6 and RCP8.5 release scenarios in the south of Kerman province. The SDSM statistical model was used for exponential microscaling of CanESM2 model output, and the Cowpat model was used to estimate the water requirement of potato plants. The results of the statistical indicators showed the high accuracy of the SDSM model and the conformity of the calibration and validation results with observational data. The mean square error of the SDSM model did not exceed 0.8% in the calibration and verification stages and was in the excellent range. The simulation results in the studied areas under RCP scenarios show an increase in the minimum temperature in the range of 0.3 to 1.3 °C, a maximum temperature in the range of 0.3 to 1.2 °C, and a decrease in precipitation in the range of -6.4 to -37.6 It will be mm. The net irrigation requirement increased in all the regions under study. The greatest increase occurred in the third period (2100-2070). On average, Kohnuj station with an average increase of 18.3% shows the highest increase, and Manujan station with 12.02% of the net irrigation requirement. Jiroft station showed the highest water demand with a 17.3% increase after Kohnuj.